2016
DOI: 10.1299/mej.16-00334
|View full text |Cite
|
Sign up to set email alerts
|

Material and heat flow analysis in thermal energy storage and transport system utilizing unused heat from bagasse boiler

Abstract: Sugar production is the main industry in Tanegashima, Japan. Whilst the sugar mill recycles sugarcane bagasse as a fuel, it concurrently generates large amounts of unused 200 °C heat during operation. Raw sugar is shipped to a refinery in Osaka for the final stages of production, which uses a city gas boiler to continuously generate a large quantity of 150 °C heat. However, factories in Tanegashima need a continuous supply of process steam at temperatures of up to 120 °C. To resolve this spatial and seasonal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Furthermore, this TES technology also enables transport of thermal energy via trucks from the power plant to sites of demand. [21] As a last case, an approach based on the carbon looping technology, i.e., the reversible reaction of calcium oxide with carbon dioxide, is evaluated. This technique is often discussed as a way of carbon dioxide removal from flue gas but is also suited very well for thermochemical energy storage due to the exothermicity of the reaction.…”
Section: Scenarios and Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this TES technology also enables transport of thermal energy via trucks from the power plant to sites of demand. [21] As a last case, an approach based on the carbon looping technology, i.e., the reversible reaction of calcium oxide with carbon dioxide, is evaluated. This technique is often discussed as a way of carbon dioxide removal from flue gas but is also suited very well for thermochemical energy storage due to the exothermicity of the reaction.…”
Section: Scenarios and Systemsmentioning
confidence: 99%
“…Yet, such adsorption‐based TES processes are suited for demand‐orientated heat provision to district heating networks. Furthermore, this TES technology also enables transport of thermal energy via trucks from the power plant to sites of demand 21. As a last case, an approach based on the carbon looping technology, i.e., the reversible reaction of calcium oxide with carbon dioxide, is evaluated.…”
Section: Scenarios and Systemsmentioning
confidence: 99%
“…10), the increase in chemicals required for agriculture was induced by technology implementation. The inputted petroleum products can be reduced to about [1] sugar mill (Ohara et al 2009(Ohara et al , 2012Ouchida et al 2017;Kikuchi et al 2016aKikuchi et al , 2017c; [2] forestry (Kikuchi et al 2016a;Kanematsu et al 2017a;Oosawa et al 2016); [3] chemical heat storage (Fujii et al 2016(Fujii et al , 2019and [4] ion-exchange resin catalyst method of biodiesel fuel production (Chen et al 2017;Shibasaki-Kitakawa et al 2010 4% of outflows (Fig. 10).…”
Section: Io Analysis and Spa Based On Customized Io Table For Tanegasmentioning
confidence: 99%
“…1. In our previous work, material and heat flow analysis of the system, we concluded that there is a potential to distribute the unused heat from the sugar mill to many factories in this island (Fujii et al, 2016), and the heat discharging process determines the overall heat availability through the heat charge and discharge cycle. Many types of heat discharging devices have been reported (Krönauer et al, 2015) (Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%